Create of a Conceptual Framework for the Use of an Agent-Based Modeling in Urban Studies with an Emphasis on the Walkable City - Zamanipoor, Masoud; Rahnama, Mohammad Rahim; Shokoui, Mohammad Ajza (Anuário do Instituto de Geociências, 2023)
Agent-based modeling by a bottom-up approach has shown that it has enough capacity to provide a natural definition for urban complicated system. During the last two decades, numerous studies have been dedicated to investigate the influence of urban policies on people’s tendency to walk using an agent-based approach. Therefore, it is considered to be the right time to meta-synthesize experiences and aggregating data into a unit in order to create a comprehensive framework for these studies. With this in mind, in this study, we aim to meta-synthesize these experiences to create a comprehensive framework in order to use agent-based modeling to investigate the influence of urban design and planning policies on people's tendency to walk. This study revealed that “basic model”, “disruptor” and “operation” made up the crucial elements of framework.